Group B streptococcus virulence factors associated with different clinical syndromes: Asymptomatic carriage in pregnant women and early-onset disease in the newborn - Schindler, Yulia; Rahav, Galia; Nissan, Israel; Treygerman, Orit; Prajgrod, George; Attia, Bracha Zukerman; Raz, Ronit; Valenci, Gal Zizelski; Tekes-Manova, Dorit; Maor, Yasmin (Frontiers in Microbiology, 2023)
Background: Group B streptococcus (GBS) harbors many virulence factors but there is limited data regarding their importance in colonization in pregnancy and early onset disease (EOD) in the newborn. We hypothesized that colonization and EOD are associated with different distribution and expression of virulence factors. Methods: We studied 36 GBS EOD and 234 GBS isolates collected during routine screening. Virulence genes (pilus-like structures-PI-1, PI-2a, PI-2b; rib and hvgA) presence and expression were identified by PCR and qRT-PCR. Whole genome sequencing and comparative genomic analyses used to compare coding sequences of colonizing and EOD isolates. Results: Serotype III (ST17) was significantly associated with EOD and serotype VI (ST1) with colonization. hvgA and rib genes were more prevalent among EOD isolates (58.3% and 77.8%, respectively; p<0.01). The pilus loci PI-2b and PI-2a were more prevalent among EOD isolates (61.1%, p<0.01), while the pilus loci PI-2a and PI-1 among colonizing isolates (89.7% and 93.1% vs. 55.6% and 69.4%, p<0.01). qRT PCR analysis revealed that hvgA was barely expressed in colonizing isolates, even though the gene was detected. Expression of the rib gene and PI-2b was twofold higher in EOD isolates compared to colonizing isolates. Transcription of PI-2a was 3-fold higher in colonizing isolates compared to EOD isolates. ST17 isolates (associated with EOD) had a smaller genome size compared ST1 and the genome was more conserved relative to the reference strain and ST17 isolates. In a multivariate logistic regression analysis virulence factors independently associated with EOD were serotype 3, and PI-1 and PI-2a were protective. Conclusions: There was a significant difference in the distribution of hvg A, rib and PI genes among EOD (serotype III/ST17) and colonizing (serotype VI/ST1) isolates suggesting an association between invasive disease and these virulence factors. Further study is needed to understand the contribution of these genes to GBS virulence.